Molecular determinants of post-mastectomy breast cancer recurrence. (December 2018) - Keene, Kimberly; King, Tari; Hwang, E.; Peng, Bo; McGuire, Kandace; Tapia, Coya; Zhang, Hong; Bae, Sejong; Nakhlis, Faina; Klauber-Demore, Nancy; Meszoely, Ingrid; Sabel, Michael; et al.
Abstract Breast cancer (BC) adjuvant therapy after mastectomy in the setting of 1–3 positive lymph nodes has been controversial. This retrospective Translational Breast Cancer Research Consortium study evaluated molecular aberrations in primary cancers associated with locoregional recurrence (LRR) or distant metastasis (DM) compared to non-recurrent controls. We identified 115 HER2 negative, therapy naïve, T 1–3 and N 0-1 BC patients treated with mastectomy but no post-mastectomy radiotherapy. This included 32 LRR, 34 DM, and 49 controls. RNAseq was performed on primary tumors in 110 patients; with no difference in RNA profiles between patients with LRR, DM, or controls. DNA analysis on 57 primary tumors (17 LRR, 15 DM, and 25 controls) identified significantly moreNF1 mutations and mitogen-activated protein kinase (MAPK) pathway gene mutations in patients with LRR (24%, 47%) and DM (27%, 40%) compared to controls (0%, 0%;p < 0.0001 andp = 0.0070, respectively). Three patients had matched primary vs. LRR samples, one patient had a gain of aNF1 mutation in the LRR. There was no significant difference between the groups forPTEN loss or cleaved caspase 3 expression. The mean percentage Ki 67 labeling index was higher in patients with LRR (29.2%) and DM (26%) vs. controls (14%, p = 0.0045). In summary, mutations in the MAPK pathway, specificallyNF1, were associated with both LRR and DM, suggesting that alterations in MAPK signaling are associated with a more aggressive tumor phenotype. Validation of these associations in tissues from randomized trials may support targeted therapy to reduce breast cancer recurrence. Genomics: NF1 mutations more frequent in recurrent breast cancer Women with breast cancer who relapse following surgery frequently harbor genomic alterations in a pathway linked to cell proliferation and anti-tumor immune responses. A USA-based team led by Funda Meric-Bernstam from the University of Texas MD Anderson Cancer Center in Houston, and Kimberly Keene from the University of Alabama at Birmingham conducted a thorough molecular analysis of tumor samples obtained from 115 women with 5 years of follow-up after a mastectomy and, oftentimes, adjuvant chemotherapy or hormonal therapy. RNA profiles did not significantly differ between women who experienced local recurrence, developed distant metastases or were still in remission. However, DNA analyses identified significantly more mutations in patients whom recurred in the mitogen-activated protein kinase cell signaling pathway, specifically NF1, implicated in cell growth and immunity. If validated, the findings support targeting this pathway to prevent disease recurrence.